The analysis of student’s junior high school perception of free sex behavior in terms of gender differences - Kholidin, Farid Imam; Putri, Elin Eria; Yandri, Hengki; Juliwati, Dosi; Erniyati, Yelni (Universitas Islam Negeri Raden Intan Lampung, 2020)
Students who are in the adolescence phase begin to show an interest in the opposite sex as shown by dating behavior. The phenomenon of dating behavior among adolescents today shows a wrong perception such as to prove love, they often engage in hand-holding, kissing, hugging and even having sex which is clearly prohibited in Islam. If the problem is not immediately revealed, it will cause serious moral damage to adolescents. The study aims to reveal students ' perception of free sex behavior in terms of gender differences. The research method used was the comparative quantitative type with the research respondents of the State Junior High School 24 Kerinci which consisted of 78 people. The research Data were revealed with a scale of free sex behavior and analyzed by using the Mann-Whitney U test. The results showed that there were different perceptions between male and female students to free sex behavior namely the score was 0,005 sig.